2007
DOI: 10.1002/qj.155
|View full text |Cite
|
Sign up to set email alerts
|

Reversed flow in the south‐Alpine Toce Valley during MAP‐IOP 8: Further analysis of latent cooling effects

Abstract: Numerical simulations are presented to examine the physical mechanisms leading to downvalley flow in the south-Alpine Toce Valley during MAP IOP 8 (20-21 October 1999), continuing a recent study by Asencio and Stein. The downvalley flow occurred during a phase of moderate precipitation, opposing the southerly (upslope) flow at higher levels that generated the precipitation. Based on sensitivity experiments with suppressed latent cooling by melting and evaporation, Asencio and Stein concluded that cooling by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In particular, they observed that the top of the radar bright band correlated with the shear level where the flow direction changed. On the other hand, Zängl (2007) conducted numerical simulations of the same event and concluded that the melting process only has a small contribution to the change of the wind flow in the valley.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, they observed that the top of the radar bright band correlated with the shear level where the flow direction changed. On the other hand, Zängl (2007) conducted numerical simulations of the same event and concluded that the melting process only has a small contribution to the change of the wind flow in the valley.…”
Section: Introductionmentioning
confidence: 95%
“…It was hypothesized that the cooling from the melting snow was associated with the change in direction of the valley flow field. The characterization of the rain-snow boundary in mountainous terrain has been addressed in several studies including Medina et al (2005), Minder et al (2011), Zängl (2007, and Minder and Kingsmill (2013). In particular, Minder et al (2011) performed numerical simulations to study the mesoscale features of the rain-snow boundary along mountainside.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of latent cooling effect in the south Alpine Toce valley Zängl (2007) argues that cooling by evaporating cloud water also influences temperature, especially if valley atmosphere continues to be subsaturated due to down valley wind. If snow melts already above the valley, the contribution of evaporating cloud water to cooling can be of major importance.…”
Section: Discussionmentioning
confidence: 99%
“…This was observed in the Toce river valley in the Italian Alps during the Mesoscale Alpine Program (MAP, Steiner et al, 2003) and during the 2010 Vancouver Olympics in the Whistler area (Thériault et al, 2012. However, Zängl (2007) using numerical simulations, suggested that the cooling by melting of snow was of less importance in creating the down-valley flow for the same event because of the impact of cooling associated with sublimation.…”
mentioning
confidence: 98%